Formation and characterization of neutral krypton and xenon hydrides in low-temperature matrices: Low-Temperature Physics and Chemistry in Cryomatrice - Lundell, Jan; Khriachtchev, Leonid; Pettersson, Mika; Räsänen, Markku (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
A family of rare-gas containing hydrides HXY (where X = Kr or Xe, Y is an electronegative fragment) is described. These molecules are experimentally prepared in low-temperature matrices by photodissociation of a hydrogen-containing HY precursor and thermal mobilization of the photodetached hydrogen atoms. The neutral HXY molecules are formed in a concerted reaction H+Y→HXY. Experimental evidence for the formation of these species is essentially based on strong infrared absorption bands that appear after annealing of the photolyzed matrices and are assigned to the X-H stretch of the HXY molecules. Computationally, the formation of these HXY molecules decreases the H-X distance by a factor of ≥2 from its van der Waals value, which emphasizes their true chemical bounding possessing both covalent and ionic contributions. The estimated dissociation energies vary from 0.4 to 1.4 eV and keep promises for forthcoming observation of these molecules in the gas phase. The experiments with the HXY molecules widen our knowledge on solid-state photolysis dynamics of hydrogen containing species. In particular, the photolysis of small HY hydrides in solid Xe seems to be a quite local process, and accompanied losses of H atoms play a minor role.